CORRELATION BETWEEN MEMORIZING AL-QUR’AN AND STUDENTS ENGLISH ACHIEVEMNT AT SMA AL MAIDAH CATAKGAYAM JOMBANG - Khudriyah Khudriyah; Jannah Riyadlul (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2025)
Learning English language skills as foreign means learning four very basic aspects, such as: listening, speaking, reading, and writing, the four language skills seems found in the al-Qur'an. This is enabling learners to correlate their achievement of both memorizing al-Qur’an and the language. This research aimed to know whether or not the correlation between achievement of memorizing al-Qur’an and English. This research is quantitative, the sample were 35 students of SMA al Maidah Catakgayam Jombang. To collect data the researcher used documentation, the data then analyzed using descriptive statistic and product moment. The result showed that the students’ memorizing al-Qur’an was categorized as middle; the students’ English achievement was categorized as middle. There is significant correlation between students’ memorizing al-Qur’an and English achievement. It is proved by the result of p-value that was 0.000 < 0.05, and the result of rxy which higher than r table 0.802 > 0.3338.